PENGARUH MOTIVASI KERJA DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PERTAMINA PATRA NIAGA KANTOR REGIONAL JAWA BAGIAN BARAT DI JAKARTA PUSAT - Syakirah Kautsari Denty; Eti Ariyanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the influence of work motivation and job training on employee performance at PT Pertamina Patra Niaga, West Java Region Office. Using a quantitative associative method with 68 respondents and multiple linear regression analysis, the results show that work motivation has a significant effect on employee performance, indicated by a t-value of 7.376, while job training also has a significant effect with a t-value of 3.556, both exceeding the t-table value of 1.997. Simultaneously, work motivation and job training significantly affect employee performance, as demonstrated by an F-value of 31.263 > F-table 3.14 with a significance level of 0.000. The R Square value of 0.490 indicates that both variables contribute 49% to employee performance, while the remaining 51% is influenced by other factors outside this study. These findings emphasize the importance of strong work motivation and well-targeted training programs in improving employee performance at PT Pertamina Patra Niaga, West Java Region Office. Keywords: Work Motivation, Job Training, Employee Performance.